2015
DOI: 10.1016/j.ijms.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Formation of sugar radical cations from collision-induced dissociation of non-covalent complexes with S-nitroso thiyl radical precursors

Abstract: A B S T R A C TA 'bio-inspired' method has been developed for generating sugar radical cations by multistage mass spectrometry (MS 4 ) experiments involving collision-induced dissociation (CID) of protonated non-covalent complexes between a sugar and an S-nitrosylated thiol amine, [H 3 NXSNO + M] + (where X = (CH 2 ) 2 , (CH 2 ) 3 , (CH 2 ) 4 , CH(CO 2 H)CH 2 and CH(CO 2 CH 3 )CH 2 ). In the first stage of CID (MS 2 ), homolysis of the S-NO bond unleashes a thiyl radical to give the non-covalent radical cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Each of the amine thiols (2-amino-1-ethanethiol; 3-amino-1-propanethiol, and 4-amino-1-butanethiol) were separately nitrosylated in 1:1 methanol–water solution with tert -butyl nitrite as described previously. The resultant reaction solutions containing the S -nitrosoamines were diluted to a 0.5 mM 1:1 methanol–water solution and directly infused into the electrospray ionization (ESI) source of a modified hybrid LTQ FT-ICR mass spectrometer at a flow rate of 5.0 μL min –1 . In the positive ion mode, the S -nitrosoammonium ions, H 3 N + (CH 2 ) n SNO were formed and the source conditions were tuned to optimize their signal.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the amine thiols (2-amino-1-ethanethiol; 3-amino-1-propanethiol, and 4-amino-1-butanethiol) were separately nitrosylated in 1:1 methanol–water solution with tert -butyl nitrite as described previously. The resultant reaction solutions containing the S -nitrosoamines were diluted to a 0.5 mM 1:1 methanol–water solution and directly infused into the electrospray ionization (ESI) source of a modified hybrid LTQ FT-ICR mass spectrometer at a flow rate of 5.0 μL min –1 . In the positive ion mode, the S -nitrosoammonium ions, H 3 N + (CH 2 ) n SNO were formed and the source conditions were tuned to optimize their signal.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…For example, intramolecular hydrogen bonding of the side chains of serine and threonine constrains free radical reaction dynamics at these residues . As part of a series of studies on the structure and reactivity of thiyl distonic ions derived from cysteine, its derivatives, and peptides, we discovered that the thiyl radical of cysteine, 1a (Scheme ), is more reactive with respect to atom abstraction reactions than homocysteine, 1b . We speculated that this may be due to differences in the strength of intramolecular hydrogen bonding …”
Section: Introductionmentioning
confidence: 99%
“…Photodissociation of saccharides derivatized with iodoaniline or saccharides with noncovalent attached iodophthalic acid produced hemolytic cleavage of the carbon–iodine bond in the attached phenyl group and thus generated highly reactive radicals 14 . Noncovalent complexation with S ‐nitrosylated thiol amine [H 3 NXSNO + M] + (where X can be (CH 2 ) 2 , (CH 2 ) 3 , (CH 2 ) 4 , CH (CO 2 H)CH 2 or CH (CO 2 CH 3 )CH 2 ) resulted in the cleavage of the S–NO bond, resulting a thiyl radical [H 3 NXS • + M] + by CID 15 ,. Further radical migration and dissociation of glycans provides useful structural information.…”
Section: Introuctionmentioning
confidence: 99%
“…Inspired by Nature"s use of enzyme radical chemistry to biocatalytically transform carbohydrate-based substrates [25][26][27][28][29][30][31], we have previously described an approach that utilizes a charged non-covalent complex between a sugar and a radical to generate a charged sugar radical [32,33]. The method (Scheme 1) involves: (i) transfer to the gas phase of a charged non-covalent complex containing a sugar and a radical precursor (an Snitrosoamine); (ii) formation of the radical cation non-covalent complex by unleashing the radical site from the precursor in preference to dissociation of the non-covalent complex (step (a) of Scheme 1); and (iii) transfer of both the radical and charge sites to the sugar upon dissociation of the radical cation non-covalent complex (step (b) of Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…to identify: (i) the site(s) of hydrogen atom abstraction; and (ii) which bonds within the sugar are cleaved upon CID of the radical cation. Based on previous studies that revealed that the best S-nitrosoamines to form the highest yield of sugar radical cations are those with a short linker [33], S-nitrosocysteamine was chosen for this work.…”
Section: Introductionmentioning
confidence: 99%